Exploring the Role of Desmos in Mathematics Learning: A Quantitative Descriptive Study - Hakim, Rahman Nul; Suhendra, Martin; Arifin, M. Zainul (Universitas Muhammadiyah Jember, 2025)
This study seeks to investigate the function of the Desmos platform in mathematics education via a quantitative descriptive methodology. The study's subjects were 32 students, evaluated on three principal dimensions: conceptual understanding, learning motivation, and student engagement in mathematics education. Data were gathered through a questionnaire aimed at assessing students' impressions of the efficacy of Desmos in facilitating the learning process. The study's results demonstrate that the utilization of Desmos positively influences all three evaluated dimensions. 50.02% of students concurred, and 38.76 percent strongly concurred that Desmos enhances their conceptual understanding of mathematics. Concerning motivation, 44.4% of students concurred and 36.9% strongly concurred that Desmos augments their motivation to study mathematics. In relation to student engagement, 40.64% of students concurred and 28.14% strongly concurred that the utilization of Desmos enhances their participation in the learning process. This study finds that Desmos significantly enhances conceptual understanding, learning motivation, and student involvement in mathematics education.